Social Cognition in Williams Syndrome: Relations between Performance on the Social Attribution Task and Cognitive and Behavioral Characteristics - Van der Fluit, Faye; Gaffrey, Michael S.; Klein-Tasman, Bonita P. (Frontiers in Psychology, 2012)
Williams syndrome (WS) is a developmental disorder of genetic origin, with characteristic cognitive and personality profiles. Studies of WS point to an outgoing and gregarious personality style, often contrasted with autism spectrum disorders; however, recent research has uncovered underlying social reciprocity difficulties in people with WS. Social information processing difficulties that underlie these social reciprocity difficulties have been sparsely examined. Participants in the current study included 24 children with WS ages 8 through 15. A lab-based measure of social perception and social cognition was administered (Social Attribution Test), as well as an intellectual functioning measure (KBIT-II) and parent reports of communication and reciprocal social skills (Social Communication Questionnaire, Social Responsiveness Scale). Relations between social cognition, cognitive abilities, and social-communication were examined. Results demonstrated relations between parent-reported social reciprocity and the typicality of the responses provided in the lab-based measure, even once variability in intellectual functioning was taken into account. Specifically, those individuals who produced narratives in response to the social attribution task (SAT) that were more similar to those described in previous studies of typically developing individuals were also reported to have fewer social reciprocity difficulties in the real world setting as reported by parents. In addition, a significant improvement in performance on the SAT was seen with added scaffolding, particularly for participants with stronger intellectual functioning. These findings indicate that difficulties interpreting the social dynamics between others in ambiguous situations may contribute to the social relationship difficulties observed in people with WS, above and beyond the role of intellectual functioning. Exploratory analyses indicated that performance by individuals with stronger intellectual functioning is improved with additional structure to a greater degree than for those with weaker intellectual functioning. Interventions that specifically target these social information processing of individuals with WS would likely be beneficial.